2021
DOI: 10.1108/sgpe-07-2020-0041
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of graduate student peer mentorship, social connectedness and well-being across four disciplines of study

Abstract: Purpose Student mental well-being is a matter of increasing concern on university campuses around the world. Social, psychological, academic and career aspects of graduate learning are enriched through peer mentorship. Peer-mentoring experiences and the impacts of these relationships on the mental well-being of graduate students remain underexplored in the scholarship of teaching and learning. The purpose of this study was to explore how engagement in formal and informal peer mentorship, as described by studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Finally, Oddone Paolucci et al. (2021) found that peer mentorship and support in graduate programs enhanced student well‐being by promoting social connectedness, a sense of belonging, increased emotional support opportunities, and improved academic motivation.…”
Section: Well‐being For Menteesmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, Oddone Paolucci et al. (2021) found that peer mentorship and support in graduate programs enhanced student well‐being by promoting social connectedness, a sense of belonging, increased emotional support opportunities, and improved academic motivation.…”
Section: Well‐being For Menteesmentioning
confidence: 99%
“…Mason and Hickman (2019) showed that peer mentors supporting international doctoral students reported several benefits, including gaining confidence, improving knowledge, and increasing socialization, which has been previously connected to increased well‐being. In Canada, researchers found that peer mentors self‐reported that participation in mentoring programs enhanced their personal growth, academic lives, and well‐being (Oddone Paolucci et al., 2021). These benefits were derived from feeling appreciated and valued by their peers.…”
Section: Well‐being For Mentorsmentioning
confidence: 99%
“…In addition, research has shown that mentoring matters for postdoctoral scholars even more than it does for graduate students (Liénard et al , 2018; Woolston, 2019). Peer mentorship among graduate students (Paolucci et al , 2021), between graduate students and postdocs (Blaney et al , 2020) and within doctoral student support groups (Panayidou and Priest, 2021) have each shown positive benefits related to increased well-being. While graduate students and postdocs have the responsibility for participating in such opportunities, institutions have a responsibility for facilitating such opportunities for participation, toward the goal of increasing belongingness, which can seek to improve mental health conditions that can be risk factors of suicidality (APA, 2022b).…”
Section: Addressing Suicidality Among Graduate Students and Postdocsmentioning
confidence: 99%
“…The informal mentoring relationships that our team developed organically during our research collaboration could be intentionally formalized by matching individuals with specific learning goals to other team members who have the capacity and expertise to provide targeted mentorship specific to these goals. Prioritizing individual and group learning can create a cultural shift that values team process and relationships (Oddone-Paolucci et al, 2021), while still promoting the traditional valued outputs of academia, including journal article publications and conference presentations.…”
Section: Promote Individual Growthmentioning
confidence: 99%